THE INFLUENCE OF FIRM SIZE, LEVERAGE AND PROFITABILITY ON HEDGING DECISIONS IN COMPANIES REGISTERED CONSUMPTION GOODS INDUSTRY ON BEI FOR THE 2021-2022 PERIOD - Handayani, Sri; Airawaty, Diana (Politeknik Siber Cerdika Internasional, 2024)
International trade activities cannot be separated from various risks that may arise in its operations. The risk that often arises in companies that carry out international trade is fluctuating foreign exchange rates. One way to deal with foreign exchange rate risk is by hedging. The aim of this research is to determine the influence of firm size, leverage and profitability on company hedging decisions. This type of research uses quantitative research. The sample is companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange for the 2021-2022 period which were selected using a purposive sampling technique. The data collection method documentation uses methods sourced from the company's official website. The data analysis technique uses logistic regression analysis. The research results show 1) there is no significant influence between firm size on the company's hedging decisions, because the sig value is 0.221 > 0.05; 2) there is no significant influence between leverage and the company's hedging decisions, because the sig value is 0.262 > 0.05; and 3) there is a significant influence between profitability and the company's hedging decisions, shown by a sig value of 0.002 < 0.05.